Associated factors to school dropout of students admitted with the condition of indigenous exception to the Universidad del Valle in 2001-II - Meneses Pardo, Ana Isabel (Sociedad y Economía, 2011)
This paper seeks to highlight the factors associated with the phenomenon of drop out students admitted by exception condition of indigenous to the University in 2001-II for which the presenter of each of the key aspects of their life path could eventually count for the episode of dropout, key aspects such as their family of origin, educational paths, educational backgrounds, both familiar and owned territories migration processes, cultural practices, indigenous self-identification, choices of academic programs, social networking and other that may count for the encounter or the socialization of the student with the academic university and in relation to the possibility of dropping out or not.